2014
DOI: 10.4049/jimmunol.1400839
|View full text |Cite
|
Sign up to set email alerts
|

Gene Targeting RhoA Reveals Its Essential Role in Coordinating Mitochondrial Function and Thymocyte Development

Abstract: Thymocyte development is regulated by complex signaling pathways. How these signaling cascades are coordinated remains elusive. RhoA of the Rho family small GTPases plays an important role in actin cytoskeleton organization, cell adhesion, migration, proliferation, and survival. Nonetheless, the physiological function of RhoA in thymocyte development is not clear. By characterizing a conditional gene targeting mouse model bearing T cell deletion of RhoA, we show that RhoA critically regulates thymocyte develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…The floxed allele contains loxP sites flanking exon 3 of the RhoA allele. To delete RhoA in vivo in T cells, RhoA flox/flox mice were mated with mice expressing Cre recombinase under the control of a CD2 proximal promoter (Jackson Laboratory, Bar Harbor, ME) . In each experiment, age‐ (8‐ to 10‐week old) and sex‐matched RhoA flox/flox CD2 Cre+ mice (hereafter, referred to as RhoA −/− or RhoA‐deficient mice) and their WT littermates (RhoA flox/flox CD2 Cre− , referred to as WT mice) were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The floxed allele contains loxP sites flanking exon 3 of the RhoA allele. To delete RhoA in vivo in T cells, RhoA flox/flox mice were mated with mice expressing Cre recombinase under the control of a CD2 proximal promoter (Jackson Laboratory, Bar Harbor, ME) . In each experiment, age‐ (8‐ to 10‐week old) and sex‐matched RhoA flox/flox CD2 Cre+ mice (hereafter, referred to as RhoA −/− or RhoA‐deficient mice) and their WT littermates (RhoA flox/flox CD2 Cre− , referred to as WT mice) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have generated a conditional RhoA‐deficient mouse line in which RhoA is specifically deleted in T cells. With this mouse model, we found that RhoA was required for coordinating mitochondrial function and thymocyte development . Moreover, RhoA orchestrated glycolysis for Th2 cell differentiation and allergic airway inflammation .…”
Section: Introductionmentioning
confidence: 91%
“…Rho family GTPases shift between the GTP‐bound ‘on’ and GDP‐bound ‘off’ states, thereby functioning as molecular switches for signal transduction in numerous cellular processes. Rho family GTPases, such as Rac1/2, 1 , 2 RhoA, 3 RhoH, 4 and Cdc42, 5 are involved in T‐cell receptor (TCR)‐mediated signal transduction; therefore, they play an important role in T‐cell development and activation. The intrinsic GTP hydrolysis activity of classical RhoGTPases is enhanced by RhoGTPase‐activating proteins (RhoGAPs).…”
Section: Introductionmentioning
confidence: 99%
“…mtDNA will be isolated by ethanol precipitation. An aliquot of homogenates was reserved for protein quantification, and mtDNA content was normalized to the protein concentration (Cheng et al, 2012; Zhang et al, 2014). Total nuclear DNA was isolated from the nuclear fraction using QIAamp DNA Mini Kit (Qiagen), according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%